Uma pesquisa sobre o uso de instrumentos de contabilidade gerencial por empresas listadas na revista eletrônica Forbes 2000 - Gabionetta, Sérgio Lima (2011)
In 1987, the work Relevance lost: the rise and fall of management accounting , by Johnson and Kaplan, was published. In such publication, the authors affirmed that the managerial accounting instruments were no longer suitable to the management and control of organizations. In March 1998, the Institute of Management Accountants (IMA) disclosed a work that described the activity known as Managerial Accounting, identifying four evolution steps in Managerial Accounting development and classifying some instruments generic expression for tools, management models and systems among these steps. The instruments belonging to the fourth step were considered as contemporary. In this scenario, this dissertation is a survey and has as basis the following research problem: The companies appearing in the list of the world‟s 2.000 largest companies, according to criteria of Forbes magazine eletronics, use contemporary managerial accounting instruments. Using such instruments is determinant for superior economic-financial performance? This work has as purposes: (1) to evidence how much the world‟s 2.000 largest companies (year of 2008) make use of contemporary managerial accounting instruments; (2) to verify whether the companies that use such instruments have superior performance over companies that use conventional instruments. The theoretical basis presents a brief description of the instruments and studies previously carried out. The information was obtained through a questionnaire sent to the companies‟ electronic addresses during the month of April 2010. The quantitative tests applied to the data were those of independent samples average significance. It was evidenced that: (1) 55.3% of the companies of the sample use contemporary managerial accounting instruments; (2) the companies that make use of such instruments do not present any higher performance over the companies that do not use them. This very same finding was achieved when the performances of the companies grouped by economic segment and origin of shareholding control were tested